Peningkatan Motivasi Belajar PAK Melalui PBL pada Materi Pelestarian Lingkungan Kelas V - Adriana Maria Obenu; Ansel Joko Prayitno (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This Classroom Action Research (CAR) was conducted to address the lack of student motivation in Catholic Religious Education (PAK) subjects, which often leads to low academic achievement. The study aimed to determine whether the application of the Problem Based Learning (PBL) model could improve students' learning motivation and academic performance, specifically in the topic "Involved in Environmental Conservation" for Grade V students (Phase C) at UPTD SD I Wue, Ngada, NTT. The research was conducted in two cycles, each comprising four stages: planning, implementation, observation, and reflection. The research subjects consisted of 20 fifth-grade students. Data collection techniques included observation, interviews, questionnaires, and documentation. In the first cycle, where the lecture method was used, the motivation level was 48.7%. In the second cycle, after implementing the PBL method, student motivation increased significantly to 94.5%. The findings showed that PBL effectively enhances learning motivation through improvements in enthusiasm, active participation in discussions, the ability to express opinions, and students' awareness of environmental preservation as an expression of faith. These results confirm that the PBL model fosters a more engaging and contextual learning experience, making it an effective approach in PAK education to build students’ moral and spiritual awareness of environmental issues. Therefore, PBL can be recommended as an alternative strategy to enhance learning motivation and faith-based understanding in Catholic Religious Education.